MBKM: ITS INFLUENCE ON THE INTEREST OF FKIP STUDENTS IN JOINING STUDENT ORGANIZATIONS - bimamasridho, Fajar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The development of education in Indonesia is fully supported by the minister of education and culture by holding educational programs for all lines of students, including students. The many benefits obtained from the Ministry of Education and Culture program are the biggest influence on the number of enthusiasts for the independent program to learn an independent campus (MBKM), both in terms of finance and conversion of courses on campus. The emergence of various Ministry of Education and Culture programs certainly affects internal campus activities, especially in student organization activities. From these problems, the researchers distributed questionnaires to find out how far the impact of the MBKM program on student interest in joining student organizations, especially at the Faculty of Psychology and Education. Questionnaires were distributed via google form to a sample of 300 students from the Faculty of Psychology and Education at Muhammadiyah University of Sidoarjo. The results showed that many students were more interested in participating in the MBKM program than student organizations because of the many benefits obtained by students such as being able to go directly to the field, gain wider experience and get pocket money, this is what makes students more interested in participating in the independent campus learning program than participating in student organization activities.